2018
DOI: 10.1007/s11244-018-1068-1
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Evolution of the La0.6Sr0.4CoO3−δ Surface Under SOFC Operating Conditions and Its Implications for Electrochemical Oxygen Exchange Activity

Abstract: Owing to its extraordinary high activity for catalysing the oxygen exchange reaction, strontium doped LaCoO 3 (LSC) is one of the most promising materials for solid oxide fuel cell (SOFC) cathodes. However, under SOFC operating conditions this material suffers from performance degradation. This loss of electrochemical activity has been extensively studied in the past and an accumulation of strontium at the LSC surface has been shown to be responsible for most of the degradation effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 49 publications
6
53
0
Order By: Relevance
“…Herein, we would like to draw attention to a recent study on a similar HT-grown LSC64 film. 56 The study observed the new growth of La containing SrO species at operation temperatures above 400 °C using an in situ near-ambient pressure XPS. Most interestingly, the new species preferentially grew on the electrochemically active Co sites.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we would like to draw attention to a recent study on a similar HT-grown LSC64 film. 56 The study observed the new growth of La containing SrO species at operation temperatures above 400 °C using an in situ near-ambient pressure XPS. Most interestingly, the new species preferentially grew on the electrochemically active Co sites.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of SOFCs and SOECs, model cells with a thin film working electrode as seen in Figure 1 are an excellent configuration for mechanistic kinetic studies, which allow simultaneous determination of electrochemical performance by measuring the current-voltage characteristics as well as observation of surface chemistry and reaction intermediates by NAP-XPS. Several of such studies were already carried out at synchrotron facilities in two-electrode cells with ceria-based electrodes [12][13][14][15] and perovskite-type electrodes [12,[16][17][18][19][20]. Recently, also the XPS investigation of operating Ni-GDC anodes in two-chamber cells and a three-electrode geometry were reported [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…By taking into account the previous deduction concerning La diffusion, the second doublet is assigned to lanthanum in the ceria environment. The classical figure of Sr 3d spectra in LSCF exhibits two contributions, the one at low binding energy corresponding to the bulk and the one at high binding energy corresponding to the surface [68][69][70]. Thus, for the tested interface, the doublet at 131.6 eV was attributed to the bulk component and the doublet at 134.2 eV to the surface component.…”
Section: Structural and Surface Chemistry Analysismentioning
confidence: 93%